About Being a Friend: Friendship and Metaphysics by Plato, Aristotle, Augustine and Albert the Great - Sánchez, Andrés Quero (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
Friendship defines an ontological scope in which being is not only regarded as the totality of things «being merely there to be used for something». That is, the area of beings which are wanted for their own sake (propter se ipsa or gratia sui), i.e. absolutely. This paper distinguishes between two different concepts of friendship which are based on two ways of understanding being: an idealistic one — as we find it in Plato’s Lysis and above all in St. Augustine’s Confessions, who maintain that thebeing of a friend as such is completely independent of his «being-there» or his «being-present» —, anda realistic one — represented by Aristotle (Nicomachian Ethics, Eudemian Ethics), who insists on thecrucial role played by «being-present» in friendship. Finally, we analyse Albert the Great’s understandingof friendship in his commentaries on the Nicomachian Ethics (both Super Ethica and Ethica) and we show how his metaphysics should be considered as Christian Aristotelism, according to the traditional interpretation, which has, as is known, been questioned for decades